Penetration test of web applications - Drahmoun, Mohammed; Chergui, Zineddine; Supervisor: Noureddine, Chikouche (University of M'sila, 2023)
In today's digital landscape, companies with web applications face an ongoing challenge of defending against cyberattacks. Proactive measures such as penetration testing play a crucial role in identifying vulnerabilities before they can be exploited. We highlighted the importance of penetration testing enabling companies to make informed decisions when evaluating weaknesses. We extensively covered common security vulnerabilities in company’s web application, including the OWASP top 10. Through a successful collaboration with the Company, we conducted a comprehensive penetration test using both manual and automated tests with tools like Burp Suite and Metasploit. Our goal was to assist the company in mitigating risks and staying ahead of cyber threats.
Keywords: Penetration testing, OWASP top 10, web applications, security vulnerabilities.